The Basmachi Movement in the Light of Soviet Archival Documents - YEŞİLOT, OKAN (TURK TARIH KURUMU, 2021)
The emergence of the Basmachi movement is usually associated with the the abolition of the Kokand government in 1918. In 1918 the insurgency also began to spread to Fergana. This was followed by Hive and Bukhara. The Basmachi groups were units formed in separate regions. Each leader had a separate territory under his control. The goal of the Basmachi was to liberate Turkestan from Soviet rule. The movement was strengthened under the leadership of Enver Pasha in 1921. With the murder of Enver Pasha in 1922, the Basmachi movement did not end, but lost power of the previous years. Under the leadership of Ibrahim Bek, the Lokai tribal leader, Basmachi movement revived in 1926. However, this resistance was ended in June 1931 and Ibrahim Bek was arrested. There have been numerous studies on the Basmachi movement in Turkey. All studies to date, however, have included the term Basmachi, the emergence and development of the movement, the causes of movement's failures and the Soviet tactics during the fight. Aims of this work was to explain the Basmachi movement through the eyes of the Soviets with archival documents in the Russian State Military Archive. These topics include the following: one of most prominent leaders of the movement, Ibrahim Bek and the mythologizing of his leadership by the people, not only Soviet administration but also views of Red Army soldiers on the struggle, reflections of Turkestan people's support for the movement on military correspondence, formation of non-Russian troops for struggle against the Basmachi and the problems of this struggle and how the Soviet administration used the clergy to eliminate popular support for the movement.
Keywords: Basmachi; Korbashi movement; Turkestan; the Red Army